Morfologia da onda de pulso da pressão intracraniana avaliada de modo não invasivo em indivíduos ativos e saudáveis após exercício de agachamento realizado com auxílio da fita de suspensão - Souza, Jean Cesar Andrade de (Universidade Federal de São Carlos, 2023)
Intracranial pressure (ICP), pressure exerted within the cranial cavity, can be altered by neurological disorders and/or physical inactivity. However, physical exercise is an important non-pharmacological tool capable of mitigating consequences caused by numerous pathologies. However, its effects on the morphology of the ICP pulse wave, especially after suspended training (ST) performed with the aid of the suspension strap (SS), are little known. Thus, we aimed to characterize the squat exercise performed with the aid of SS and its hemodynamic consequences and ICP based on a non-invasive evaluation method, through metrics of indirect prediction of the state of intracranial dynamics. The sample consisted of 30 individuals (15 men; 15 women), between 18 and 40 years-old, physically active and adapted to resistance exercises. Blood analysis, anthropometric assessments and incremental test to determine the point of highest oxygen consumption (VO2peak) were performed, followed by familiarization and ST session. This session consisted of 3 series of squats performed with the aid of the SS, performed for 1 minute, with intervals between series of 1 minute, in which pre, during and immediately post-exercise (3rd, 6th, 9th and 12th minute/post-session) glycemia, blood lactate concentration ([Lac]), oxygen saturation (SpO2), energy expenditure (EE), heart rate (HR), blood pressure (BP), ICP through metrics indirect prediction of the state of intracranial dynamics, such as: the ratio between the second and the first peak of the ICP pulse wave (P2/P1) and Time to Peak (TTP); in addition to the session's subjective perception of exertion (SPE) (30 minutes/post-session). Data were submitted to Student's T test to compare men and women (body composition, lipid profile, fasting blood glucose and VO2peak). With the unified group, the Anova One-Way variance test (remaining variables) and Bonferroni's post hoc test of variance were performed, followed by Pearson's correlation (all variables evaluated). The results are presented as mean ± standard error of the mean and percentage variation, for a significance level of 5%. The work load (WL) of the exercise was 4,182.60±139.30A.U., with the volunteers reaching during the same 46.66±1.63% of VO2peak and 66.99±1.80% of maximum HR established during the incremental test, still reporting a SPE of 10.53±0.30A.U. There was a significant increase in HR, systolic BP, mean BP (MAP), [Lac] and EE and a decrease in SpO2, P2/P1 and TTP compared to rest. WL was positively correlated with body mass (r=0.999;p<0.001), Body Mass Index (BMI) (r=0.764;p<0.001), [Lac] (r=0.503;p<0.001), EE (r=0.778;p<0.001) and negatively with P2/P1 (r=-0.539;p<0.001) and TTP (r=-0.438;p<0.001). There was a correlation between [Lac] and EE (r=0.731;p<0001), and between the latter and body mass (r=0.644;p<0.001) and BMI (r=0.394;p=0.031). We also verified a negative correlation between MAP and P2/P1 (r=-0.367;p<0.001) and MAP and TTP (r=-0.458;p<0.001), indicating maintenance of static cerebral autorregulation in the face of effort caused by exercise. We conclude that the ST protocol altered the hemodynamics and metabolism of the volunteers, modifying the morphology of the ICP pulse wave, which, added to the correlation with MAP, indicated an increase in intracranial compliance and maintenance of static cerebral autorregulation in the face of the effects caused by exercise.
Pulse wave morphology of intracranial pressure assessed non-invasively in active and healthy individuals after squatting exercise performed with the aid of the suspension strap
Keywords: Dinâmica intracraniana; Exercício físico; Hemodinâmica; Metabolismo; Pressão intracraniana; Treinamento suspenso; Intracranial dynamics; Physical exercise; Hemodynamic; Metabolism; Intracranial Pressure; Suspension Training; CIENCIAS BIOLOGICAS::FISIOLOGIA